2011
DOI: 10.1111/j.1540-8175.2011.01594.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolumetric Echocardiographic Indices of Right Ventricular Systolic Function: Validation with Cardiovascular Magnetic Resonance and Relationship with Functional Capacity

Abstract: Strain by speckle tracking echocardiography and strain rate by tissue velocity imaging may offer complementary information in the evaluation of RV contractility and its functional effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 31 publications
6
39
0
3
Order By: Relevance
“…These findings are similar to other studies which included athletes or general population, and which used different imaging techniques such as 2DE, 3DE or even MRI [31][32][33]. Leong et al [34] found significant correlation between peak oxygen uptake and echocardiographic parameters of right-ventricular systolic function such as right-ventricular ejection fraction, tricuspid annular plane systolic excursion, s 0 and right-ventricular tissue Doppler strain rate. However, the authors did not find statistically significant correlation between VO 2 max and right-ventricular speckle tracking strain [34].…”
Section: Right-ventricular Mechanics and Exercise Capacitysupporting
confidence: 88%
See 1 more Smart Citation
“…These findings are similar to other studies which included athletes or general population, and which used different imaging techniques such as 2DE, 3DE or even MRI [31][32][33]. Leong et al [34] found significant correlation between peak oxygen uptake and echocardiographic parameters of right-ventricular systolic function such as right-ventricular ejection fraction, tricuspid annular plane systolic excursion, s 0 and right-ventricular tissue Doppler strain rate. However, the authors did not find statistically significant correlation between VO 2 max and right-ventricular speckle tracking strain [34].…”
Section: Right-ventricular Mechanics and Exercise Capacitysupporting
confidence: 88%
“…Leong et al [34] found significant correlation between peak oxygen uptake and echocardiographic parameters of right-ventricular systolic function such as right-ventricular ejection fraction, tricuspid annular plane systolic excursion, s 0 and right-ventricular tissue Doppler strain rate. However, the authors did not find statistically significant correlation between VO 2 max and right-ventricular speckle tracking strain [34]. Considering the results of our previous investigation, among the untreated hypertensive patients, which demonstrated that BP level was independently associated with right-ventricular deformation [14], and findings of the present study, we could hypothesize that BP primarily affects cardiac function and mechanics, which further causes deterioration of functional capacity.…”
Section: Right-ventricular Mechanics and Exercise Capacitymentioning
confidence: 98%
“…RV function was evaluated by tricuspid annular plane systolic excursion (TAPSE), which was displayed by applying an M-mode algorithm to the lateral tricuspid annulus in the RV apical view. This approach to the assessment of RV function was chosen as a widely available and highly feasible one, which is recommended as a routine part of RV evaluation 9. RV impairment was defined as TAPSE≤14 mm, as this cut-off has demonstrated important prognostic value in heart failure patients 10.…”
Section: Methodsmentioning
confidence: 99%
“…We aimed to assess the progressive cardiac responses during and after the race by echocardiographic evaluation conducted pre-, mid-, and postrace. To obtain insight into LV intrinsic regional myocardial function, we used 2D Speckle Tracking Echocardiography (STE) to assess regional LV (2,10) and right ventricular (RV) strains (15). We hypothesized that, due to the specific physiological processes of MUMs, especially PV expansion, several days of running in mountains would induce specific and progressive alterations of cardiac function.…”
mentioning
confidence: 99%